2021
DOI: 10.1101/2021.08.02.21261374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of a drug-free, barrier-forming nasal spray for allergic rhinitis: randomized, open-label, crossover noninferiority trial

Abstract: BackgroundSymptoms of allergic rhinitis can be reduced by nonpharmacological nasal sprays that create a barrier between allergens and the nasal mucosa. A new nasal spray (AM-301) containing the clay mineral bentonite was tested for its ability to reduce symptoms to grass pollen.MethodsThis open label, crossover, noninferiority trial compared the efficacy and safety of AM-301 to that of hydroxypropyl methylcellulose (HPMC; Nasaleze Allergy Blocker), an established barrier method. Adults with seasonal allergic r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The medical devices used in the study are commercially available in some countries. A preprint version of this article is available on medRxiv [32].…”
Section: Statement Of Ethicsmentioning
confidence: 99%
“…The medical devices used in the study are commercially available in some countries. A preprint version of this article is available on medRxiv [32].…”
Section: Statement Of Ethicsmentioning
confidence: 99%
“…However, there was no difference between AM-301 and its matrix, suggesting that bentonite is not responsible for this effect, which may rather be due to the viscosity of the formulation. Importantly, safety and tolerability of AM-301 were further confirmed in a clinical investigation with 36 allergic rhinitis patients, where AM-301 was well tolerated and was considered safe for human use [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…AM-301 was applied once every 24 h, whereas in patients, 2–3 administrations per day would be likely. Indeed, clinical data from an allergen exposure chamber study showed that AM-301 well tolerated and provided a protective effect lasting more than 3 h [ 33 ]. The encouraging results of these studies in which the effect of AM-301 was shown for both viruses and allergens imply a mechanism of action likely to be applicable to diverse airborne particles and call for further investigations in vivo and in humans, to further evaluate AM-301 as a medical device with a broad spectrum of action against as other viruses, allergens, and possibly pollutants.…”
Section: Discussionmentioning
confidence: 99%